Catastrophe Models for Cognitive Workload and Fatigue in a Vigilance Dual Task. (June 2014) - Guastello, Stephen J.; Malon, Matthew; Timm, Paul; Weinberger, Kelsey; Gorin, Hillary; Fabisch, Megan; Poston, Kirsten
Objective: This study investigated two cusp catastrophe models for cognitive workload and fatigue for a vigilance dual task, the role of emotional intelligence and frustration in the performance dynamics, and the dynamics for individuals and teams of two participants. Background: The effects of workload, fatigue, practice, and time on a specific task can be separated with the two models and an appropriate experimental design. Group dynamics add further complications to the understanding of workload and fatigue effects for teams. Method: In this experiment, 141 undergraduates responded to target stimuli that appeared on a simulated security camera display at three rates of speed while completing a jigsaw puzzle. Participants worked alone or in pairs and completed additional measurements prior to or after the main tasks. Results: The workload cusp verified the expected effects of speed and frustration on change in performance. The fatigue cusp showed that positive and negative changes in performance were greater if more work on the secondary task was completed and whether the participants who started with the fast vigilance condition demonstrated less fatigue. Conclusion: The results supported the efficacy of the cusp models and suggested, furthermore, that training modules that varied speed of presentation could buffer the effects of fatigue. Application: The cusp models can be used to analyze virtually any cognitively demanding task set. The particular results generalize to vigilance tasks, although a wider range of conditions within vigilance tasks needs to be investigated further.